Analysis of The Effect of Product, Price, Promotion, And Location on Customer Loyalty of Tenun Ikat - Sefnat Aristarkus Tang; Yustina Maro (Jurnal Ilmiah Manajemen dan Bisnis, 2023)
This study aims to determine the effect of the product, price, promotion, and location on customer loyalty of ikat in Baranusa Village, Pantar Barat District, Alor Regency, either partially or simultaneously. Customer loyalty is a positive attitude shown by customers towards goods or services by repurchasing the products or services offered by the company and recommending them to friends and family. Loyal customers can indirectly help companies promote products or services to those closest to them.Data was collected using a questionnaire using 30 respondents. Data analysis used descriptive statistics, research instrument tests, multiple linear regression, t-test, and F test. The results showed that partially the product had a significant positive effect on customer loyalty, the price had a significant positive effect on customer loyalty, and the promotion had a significant positive effect on customer loyalty. , and location have a significant positive effect on customer loyalty. Simultaneously product, price, promotion, and location have a significant positive effect on customer loyalty.